2019
DOI: 10.1071/ah18093
|View full text |Cite
|
Sign up to set email alerts
|

Robotic colorectal surgery in Australia: a cohort study examining clinical outcomes and cost

Abstract: Objective The aim of this study was to compare robotic versus laparoscopic colorectal operations for clinical outcomes, safety and cost. Methods A retrospective cohort study was performed of 213 elective colorectal operations (59 robotic, 154 laparoscopic), matched by surgeon and operation type. Results No differences in age, body mass index, median American Society of Anesthesiologists score or presence of cancer were observed between the laparoscopic or robotic surgery groups. However, patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…In 2019, Wilkie et al published a study comparing 59 robotic colorectal operations to 154 equivalent laparoscopies and found longer procedure times, length of stay, more frequent intensive care admission and higher consumable costs 16 . Their findings stand in contrast to ours, but we suspect this is due to several aspects.…”
Section: Discussioncontrasting
confidence: 62%
“…In 2019, Wilkie et al published a study comparing 59 robotic colorectal operations to 154 equivalent laparoscopies and found longer procedure times, length of stay, more frequent intensive care admission and higher consumable costs 16 . Their findings stand in contrast to ours, but we suspect this is due to several aspects.…”
Section: Discussioncontrasting
confidence: 62%
“…Only one included study 22 reported hernia rates and none reported pain scores. Robotic colorectal surgery has been shown to be significantly more costly compared to laparoscopic surgery in Australian cohorts with equivalent clinical outcomes 45,46 . Given the high initial overhead and running costs associated with establishing a robotics program, future health economic studies should be conducted with a view to determining its cost‐effectiveness compared to standard care.…”
Section: Discussionmentioning
confidence: 99%
“…reported 1.7% 90 days mortality and the ROLARR mortality rate was 0.9%; all deaths were related to septic complications [13,21] [15]. Other studies report a range between 4 and 7 days [20,[22][23][24][25]29].…”
Section: Morbidity and Mortalitymentioning
confidence: 97%